2019 IEEE Winter Conference on Applications of Computer Vision (WACV) 2019
DOI: 10.1109/wacv.2019.00110
|View full text |Cite
|
Sign up to set email alerts
|

Ventral-Dorsal Neural Networks: Object Detection Via Selective Attention

Abstract: Deep Convolutional Neural Networks (CNNs) have been repeatedly proven to perform well on image classification tasks. Object detection methods, however, are still in need of significant improvements. In this paper, we propose a new framework called Ventral-Dorsal Networks (VDNets) which is inspired by the structure of the human visual system. Roughly, the visual input signal is analyzed along two separate neural streams, one in the temporal lobe and the other in the parietal lobe. The coarse functional distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Object detection and localization is also performed in the visual cortex in the ventral and dorsal stream (Desimone and Duncan, 1995). Artificial neural networks like CNNs have taken inspiration from that and are now highly-performant for this task (Ebrahimpour et al, 2019). In such approach, several radar processing steps (target detection, clustering and classification) can be realized by a single artificial neural network as demonstrated by Pérez et al (2019).…”
Section: Clustering/peak Groupingmentioning
confidence: 99%
“…Object detection and localization is also performed in the visual cortex in the ventral and dorsal stream (Desimone and Duncan, 1995). Artificial neural networks like CNNs have taken inspiration from that and are now highly-performant for this task (Ebrahimpour et al, 2019). In such approach, several radar processing steps (target detection, clustering and classification) can be realized by a single artificial neural network as demonstrated by Pérez et al (2019).…”
Section: Clustering/peak Groupingmentioning
confidence: 99%
“…Inspired by separate pathways in the visual cortex, Ebrahimpour et al [12] proposed a ventral-dorsal network for detecting objects. The Ventral Net removes backgrounds using a selective activation cue.…”
Section: Related Workmentioning
confidence: 99%
“…The ventral stream deals with the "what" of object recognition; and the dorsal stream deals with the "where" of spatial and motion information. This decomposition into specialised models has been exploited in applications such as object detection [17] and semantic grasping [28] in robotics. At the intersection of neuroscience and self-supervised learning, [2] showed that a two branch neural network trained with the CPC [41] loss on videos leads to dorsal and ventrallike pathways emerging.…”
Section: Related Workmentioning
confidence: 99%